Primitive Neuroectodermal Tumor in the Spinal Cord of a Brahman Crossbred Calf - Berrocal Avila, Alexis (2005)
A variety of embryonal tumors of the central nervous system, typically malignant and occurring in young individuals, are recognized in humans and animals. This report describes an invasive subdural but predominantly extramedullary primitive neuroectodermal tumor developing at the lumbosacral junction in a 6-month-old Brahman crossbred calf. The tumor was composed of spindloid embryonal cells organized in interlacing fascicles. The cells had oval to elongate or round hyperchromic nuclei, single to double nucleoli, and scant discernible cytoplasm. Immunohistochemical staining for neuron-specific enolase, synaptophysin, and S-100 protein and formation of pseudorosettes suggested neuronal and possibly ependymal differentiation.